O020 Long noncoding RNA H19X is a master regulator of extracellular matrix production in systemic sclerosis. (21st February 2018) - Pachera, E; Assassi, S; Salazar, G; Frank-Bertoncelj, M; Distler, J; Kania, G; Distler, O
Abstract : Introduction: We have recently identified a novel, yet undescribed lncRNA, H19X, which was upregulated in the skin and lung of patients with SSc in a TGFβ dependent manner. Objectives: To characterise the function and the molecular mechanism of H19X in Systemic Sclerosis (SSc). Methods: The function of H19X was investigated in skin fibroblasts by knocking down H19X with locked nucleic acid oligonucleotides (LNA GapmeRs) and by using the following methods microarray analysis, immunofluorescence, Sircol, contraction assay, ELISA, Western blot (WB), in situ hybridization using Stellaris FISH probes and Assay for Transposase-Accessible Chromatin using sequencing (ATAC-seq). Results: Microarray analysis (n=5) showed that after H19X silencing collagen catabolic process, extracellular matrix organisation and extracellular matrix disassembly were among the pathways with highest number of enriched genes. Sircol assay for pan-collagen production (n=5, p<0.05), ELISA for pro-collagen Iα1 (n=5, p<0.05) and WB analysis for fibronectin (n=7, p<0.05) confirmed the importance of H19X in the regulation of extracellular matrix components. Additionally, silencing of H19X significantly impaired αSMA fibre formation, stress fibre formation as well as cell contractility strongly suggesting an important role of H19X in the development of the myofibroblast phenotype. Cell fractionation showed that TGFβ induced expression of H19X is localised mainly into the nucleus. In situ hybridization confirmed H19X localization as mainly nuclear and within a defined spot indicating that H19X could influence gene expression by interacting directly with the chromatin (n=4). TFAP2a was identified as the transcription factor with the strongest difference of occupied binding sites after H19X downregulation. Conclusions: The novel lncRNA H19X appears to be a condition sine qua non for the profibrotic effects of TGFβ. Mechanisms of action of the profibrotic effects of H19X point to epigenetic regulation of the transcription factor. LncRNA open new perspectives in the pathogenesis of fibrotic diseases. Disclosure of interest: E. Pachera: None declared, S. Assassi: None declared, G. Salazar: None declared, M. Frank-Bertoncelj: None declared, J. Distler Grant/research support from: 4D Science, 1, Anamar, Active Biotech, Array Biopharma, BMS, Bayer Pharma, Boehringer Ingelheim, Celgene, GSK, Novartis, Sanofi-Aventis, UCB, 2, Actelion, Active Biotech, Anamar, Bayer Pharma, Boehringer Ingelheim, Celgene, Galapagos, GSK, Inventiva, JB Therapeutics, Medac, Pfizer, RuiYi and UCB, Consultant for: 4D Science, 1, Anamar, Active Biotech, Array Biopharma, BMS, Bayer Pharma, Boehringer Ingelheim, Celgene, GSK, Novartis, Sanofi-Aventis, UCB, 2, Actelion, Active Biotech, Anamar, Bayer Pharma, Boehringer Ingelheim, Celgene, Galapagos, GSK, Inventiva, JB Therapeutics, Medac, Pfizer, RuiYi and UCB, G. Kania Grant/research support from: Bayer, O. Distler Grant/research support from: Actelion, Bayer, BiogenIdec, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Sinoxa and UCB, 2, Actelion, Bayer, BiogenIdec, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Sinoxa and UCB